Surveillance of adverse events following the introduction of inactivated poliovirus vaccine made from Sabin strains (sIPV) to the Chinese EPI and a comparison with adverse events following inactivated poliovirus vaccine made from wild strains (wIPV) in Jiangsu, China - Guodong Kang; Fenyang Tang; Zhiguo Wang; Ran Hu; Jing Yu; Jun Gao (Taylor & Francis Group, 2021)
One dose of inactivated poliovirus vaccine (IPV) was introduced into the Chinese Expanded Program on Immunization (EPI) in 2016. IPV made from Sabin strains (sIPV) was newly licensed in China and its safety has been concerned. This study aimed to evaluate the safety of sIPV and provide a comparison with conventional IPV made from wild strains (wIPV). We collected all IPV-related AEFI reports in Jiangsu from the Chinese National Adverse Events Following Immunization Information System (CNAEFIS) for 2016-2019. We obtained the administered doses of IPV from the Jiangsu provincial Electronic Immunization Registries System (JSEIRS). The AEFI reporting rates per 100,000 doses of vaccine administered were compared for sIPV and wIPV. A total of 699 sIPV and 908 wIPV AEFI cases were collected by CNAEFIS in Jiangsu during 2016-2019. The overall AEFI reporting rates were 53.02 per 100,000 doses and 41.25 per 100,000 doses for sIPV and wIPV, respectively (P < .001). For both sIPV and wIPV, the AEFIs were mainly classified as common adverse reactions. The reporting rate of common adverse reactions was higher for sIPV than for wIPV (P < .001). The most frequently reported symptoms/signs were fever, persistent crying, injection site erythema/swelling, rash, and injection site induration. Only 1.14% of sIPV-associated and 2.31% of wIPV-associated AEFI cases were diagnosed as serious. No difference in reporting rate was observed for serious AEFIs (P = .272). sIPV has a favorable safety profile, although it exhibits a slightly higher reporting rate of common adverse reactions than wIPV.